Numerical Modeling on Dynamic Characteristics of Jointed Rock Masses Subjected to Repetitive Impact Loading - Jie Liu; Yan-Bin Song; Yue-Mao Zhao (Shock and Vibration)
A discrete element method code was used to investigate the damage characteristics of jointed rock masses under repetitive impact loading. The Flat-Joint Contact Model (FJCM) in the two-dimensional particle flow code (PFC2D) was used to calibrate the microparameters that control the macroscopic behavior of the rock. The relationship between macro- and microparameters by a series of uniaxial direct tension and compression numerical tests based on an orthogonal experimental design method was obtained to calibrate the microparameters accurately. Then, the Synthetic Rock Mass (SRM) method that incorporates joints into the calibrated particle model was used to construct large-scale jointed rock mass specimens, and the repetitive drop hammer impact numerical tests on SRM specimens with different numbers of horizontal joints and dip angle joints were carried out to study the damage evolution, stress wave propagation, and energy dissipation characteristics. The results show that the greater the number of joints, the greater the number of cracks generated, the greater the degree of damage, and the more energy dissipated for rock masses with horizontal joints. The greater the dip angle of joints, the less the number of cracks generated, the less the degree of damage, and the less energy dissipated for rock masses with different dip angles of joints. The impact-induced stress waves will be reflected when they encounter preexisting joints in the process of propagation. When the reflected stress waves meet with subsequent stress waves, the stress waves will change from compressional waves to tensile waves, producing tensile damage inside rock masses.